Background and Rationale for the Need for Suryomentaraman Counseling - Isnaul Khoiriyah; Faizatul Mufliha; Nor Hikmah; Zikrilla Amaliya; Finza Triyas Agustin; Rusmiyati (Feelings: Journal of Counseling and Psychology, 2026)
a counseling approach based on local values ​​through the teachings of the soul of Ki Ageng Suryomentaram. This approach focuses on the cultivation of feelings as a means to understand oneself and overcome life's problems, by placing humans as creatures driven by feelings, not just thoughts. Within this framework, counseling not only aims to solve emotional problems, but also directs individuals towards a happier, healthier, and more prosperous life. Suryomentaraman counseling reinforces the importance of self-awareness and awareness of inner change as a path to spiritual fortitude. Counselors in this approach act as reminders that help clients accept life conditions openly and be aware of the nature of human desires that are constantly changing. The principle of the present, namely accepting "what is now, here, and like this", is the main foundation in this counseling process. This approach also rejects dependence on western concepts, and prioritizes spiritual and introspective values ​​typical of Javanese culture. Therefore, counseling based on the soul of the soul is a relevant alternative for efforts to improve mental well-being in the context of Indonesian society which is rich in local wisdom.